SUPPORTING THE PREVENTION OF PREECLAMPSIA IN PREGNANT WOMEN THROUGH PRENATAL YOGA RELAXATION TRAINING - Tiyas, Dwi Wahyuning (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2025)
Blood pressure above 140 mmHg in pregnant women is an indicator of preeclampsia during pregnancy. Hypertension experienced by pregnant women can lead to complications such as seizures (eclampsia), cardiovascular disorders, stroke, and even maternal death. Based on observations of pregnant women in Lantek Timur Village, Galis district, Bangkalan Regency, it was found that 28% of pregnant women were at risk of developing preeclampsia. This highlights the need for preventive efforts to reduce blood pressure, inflammation of endothelial function, and physical stress during pregnancy. One effective approach to promote relaxation, calmness, and comfort in pregnant women is through prenatal yoga relaxation exercises. Prenatal yoga is a productive solution that helps return the body to a calmer state. The combination of physical techniques, structured breathing, and meditation stimulates a sense of well-being as mothers face the challenges of pregnancy. Because this technique requires repeated practice, health education and facilitated prenatal yoga sessions are necessary and can be incorporated into maternal health classes as an additional activity. Health education on the prevention of preeclampsia through prenatal yoga had been implemented in a planned manner. Educational media, including PowerPoint presentations, instructional videos, and pre- and post-tests, were provided. The results showed that most pregnant women had a good level of knowledge, with scores above 76% on the post-test. The facilitated implementation of prenatal yoga exercises was conducted through demonstration by facilitators, the distribution of booklets as guides for home practice, and the use of audiovisual media. During the sessions, all participating pregnant women were able to follow and imitate the prenatal yoga movements. Furthermore, every participant expressed that they felt calm and relaxed, and stated a desire to continue practicing prenatal yoga independently at home.